Factors Influencing User Satisfaction with Family Parental Services in Independent Midwife Practices - Ni Ketut Noriani; Ni Kadek Neza Dwiyanti; Ni Wayan Sri Rahayuni (GLOBAL HEALTH SCIENCE GROUP, 2026)
This study aims to analyze the factors influencing satisfaction with family planning (FP) services at Midwife Tatik Sulistriani's Independent Practice in Denpasar City. The variables studied included service quality, staff attitude, service facilities, user knowledge, and service time, with user satisfaction as the dependent variable. This study used a quantitative analytical design with a cross-sectional approach. The sample was drawn using the Lemeshow formula, with 196 respondents. Data were collected through a structured questionnaire based on standardized SOPs. Data were analyzed using the chi-square test and logistic regression to determine the relationships between variables and the dominant factors influencing satisfaction. The study showed that all independent variables significantly influenced family planning (FP) user satisfaction (p < 0.05). Service quality was the most dominant factor influencing satisfaction, followed by staff attitude, service facilities, user knowledge, and service time. This suggests that family planning user satisfaction is influenced by comprehensive service aspects, including service quality, staff professionalism, facility availability, user understanding of family planning, and service time efficiency. To increase the satisfaction of family planning users at Midwife Tatik Sulistriani's Independent Practice, it is necessary to improve the quality of services comprehensively, train staff to improve attitudes and communication, provide adequate facilities, educate users regularly, and manage service time more efficiently.